Optimisasi Hiperparameter Tuning pada Metode Support Vector Machine untuk Klasifikasi Tingkat Kematangan Buah Kopi - Rusman, Juprianus; Haryati, Berlian Zetikarya; Michael, Aryo (J-Icon : Jurnal Komputer dan Informatika, 2023)
This study aims to develop an optimal classification model to identify the maturity level of coffee fruit based on color features of coffee fruit images. The color features red, green and blue in RGB color space and hue, saturation and value in HSV color space are extracted from the coffee fruit image and used as input for the support vector machine (SVM) classification model. In order to optimize the performance of SVM, hyperparameter tuning is used with the grid search method to determine the best parameters in the classification model built. By using 180 training images in determining the optimum parameters, the hyperparameter tuning results of the grid search method are obtained at cross validation (cv) = 6, cost (C) = 1000, gamma (γ) = 0.001, and kernel = linear. Then the optimum parameters are used as an SVM model to classify 45 test images into three different classes, namely ripe, half ripe and raw. Based on the evaluation with confusion matrix, it can be concluded that the built model has good performance with 98% accuracy. This indicates that the model is able to distinguish the three classes with a low error rate. With this ability, the model built has great potential in the agricultural industry to support the use of technology in agriculture, especially coffee farming such as post-harvest fruit processing. This model can be developed on a maturity level sorting machine.